2012
DOI: 10.13005/ojc/280117
|View full text |Cite
|
Sign up to set email alerts
|

Enviromentaly Friendly Functionalization of Carboxylated Shortend Multi-Wall Nanotubes with Sunset Yellow Dye

Abstract: In this paper, the chemical functionalization of carboxylated shortend multi-walled carbon nanotubes (MWNT-COOH) by sunset yellow dye via esterification method in water have been investigated.The functionalized MWNTs were characterized by Fourier Transform Infrared spectroscopy (FT-IR), Raman spectroscopy, elemental analysis,scanning electron microscopy (SEM), Defunctionalization test and UV analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Acid solution mixture will attack the double bonding of the carbon in the hexagonal carbon at region 500-1000 cm -1 [2]. It reduces the intensity of the peak elucidates presence of large number, it also said that the peaks around 600 and 800 cm -1 are originated from the C=C bond from aromatic rings form during the oxidation process [17]. While in c), the two prominent peaks at around 1216 cm -1 and 1366 cm -1 proved the successfulness of the citric acid treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Acid solution mixture will attack the double bonding of the carbon in the hexagonal carbon at region 500-1000 cm -1 [2]. It reduces the intensity of the peak elucidates presence of large number, it also said that the peaks around 600 and 800 cm -1 are originated from the C=C bond from aromatic rings form during the oxidation process [17]. While in c), the two prominent peaks at around 1216 cm -1 and 1366 cm -1 proved the successfulness of the citric acid treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Followed that, Raman spectroscopy was performed for MWCNTs compared to their drug conjugated form. [27][28][29] Nanofluid Preparation…”
Section: Nano-drug Characterizationmentioning
confidence: 99%
“…Several studies demonstrated the possibility of using CNTs as a nanocarrier for TB drug delivery and were conducted to overcoming on antibacterial resistance of TB. 15,28 One study in 2019 reported that chitosan-functionalized CNTs could increase the drug permeability of INH in the treatment of TB in the bone and wound tissues. 33 Also, Barros et al, 34 demonstrated the efficacy of naphthoimidazoles together with INH and rifampin, as the main drugs for controlling tuberculosis.…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%